Barriers to contraceptive careseeking: the experience of Eritrean asylum-seeking women in Israel. Issue 2 (17th February 2020) - Gebreyesus, Tsega; Gottlieb, Nora; Sultan, Zebib; Ghebrezghiabher, Habtom Mehari; Tol, Wietse; Winch, Peter J.; Davidovitch, Nadav; Surkan, Pamela J.
ABSTRACT: Objectives: In recent years, there has been a mass migration of Eritreans (many seeking political asylum) into Israel after precarious irregular movement across international borders. This study qualitatively explores the structural barriers to family planning (i.e. contraceptive services) for Eritrean women in Israel that are rooted in their temporary legal status and the patchwork of family planning services. Design/Methods: From December 2012 to September 2013, we interviewed 25 key informants (NGO workers, researchers, Eritrean community activists, International NGO representatives and Ministry of Health officials) and 12 Eritrean asylum seekers. We also conducted 8 focus groups with Eritrean asylum seekers. Data were analyzed using both inductive and deductive coding. Results: We identified 7 main barriers to accessing family planning services: (1) distance to health facilities; (2) limited healthcare resources; (3) fragmentation of the healthcare system; (4) cost of contraceptive services; (5) low standard of care in private clinics; (6) discrimination; and (7) language barriers. Conclusion: The political, economic and social marginalization of Eritrean asylum-seeking women in Israel creates structural barriers to family planning services. Their marginalization complicates providers' efforts (NGO and governmental) to provide them with comprehensive healthcare, and hinders their ability to control their sexual and reproductive health. Failure to act on this evidence may perpetuate the pattern of unwanted pregnancies and social and economic disparities in this population.